Comfort and the tourism accommodation sector: A central, yet under-studied issue. (August 2018) - Nagy, Gabriella; Carr, Neil
Highlights: Comfort is poorly researched in hospitality and tourism. Comfort is a complex concept. Comfort is a constantly evolving entity. Abstract: While comfort as a word is utilised extensively within the hospitality and tourism industry there has been little research undertaken on comfort in the context of hospitality or tourism. Moreover, those studies that have examined comfort within a hospitality or tourism context have applied a very narrow interpretation of comfort. Consequently, this article draws attention to the notion of comfort, more specifically domestic comfort and its complexity, and highlights its importance in the evolution of tourist accommodation. In concluding, it is suggested that future research in hospitality and tourism studies should be grounded on the recognition of the complexity of comfort and research it is a holistic manner in order to aid the development of the hospitality sector in its pursuit of customer satisfaction.